Late Pleistocene–Holocene multi-decadal patterns of extreme floods in NW Iberia: The Duero River palaeoflood record - Benito Gerardo; Greenbaum Noam; Medialdea Alicia; Calle Mikel; Sanchez-Moya Yolanda; Machado Maria; Ballesteros-Cánovas Juan Antonio; Corella Juan Pablo (Elsevier Ltd, 2025)
Extreme floods are anticipated to become more frequent in a future warmer climate. However, the long-term alterations in flood patterns across different regions of Europe remain unclear. In this study, we present a 15,000-year record of extreme floods in the Duero River, located in the southwestern Atlantic region. We analysed slackwater flood sediments, quantified the discharge and timing of individual flood beds over millennial time scales, and identified their potential climate influences. The composite record includes at least 62 floods grouped into ten flood-rich periods (with an average duration of 230 years). A high-frequency phase of moderatemagnitude floods (>10 events) occurred at ~11.6–11.5 ka, following a period of reduced flood activity during the Younger Dryas. Similar clusters of Early Holocene floods (10.8–10.3 ka, 9.5 ka) coincided with or preceded meltwater pulses from the North Atlantic. The absence of palaeoflood records with discharges exceeding 6100 m3 /s during the Mid-Holocene suggests a decline in winter hydro-meteorological extremes. High flood magnitudes were recorded during transition periods toward cooler and wetter conditions at 4.4, 2.3, 0.5, and 0.11 ka with discharges ranging from 7600 to 10,000 m3 /s. These periods were interpreted as indicative of a southward shift in cyclone tracks in Europe driven by negative phases of the North Atlantic Oscillation (NAO). Conversely, flood magnitudes decreased during past warmer climate conditions (1.7 ka, 0.9 ka, and the present), although flood frequency remained high. The current decline in flood frequency reflects an increase in flood regulation due to dams, but it is also consistent with the prevailing positive trend in the NAO observed over the last 40 years.